Clinical outcomes and safety of remdesivir in hospitalized individuals with COVID-19, with or without severe renal impairment - Min-Chi Chang; Ping-Feng Wu; Yu-Chien Ho; Wen-Ying Lin; Chia-Ying Wu; Szu-Yu Liu; Chia-Jen Liu; Yi-Tsung Lin (Elsevier, 2024)
Background: The use of remdesivir in patients with coronavirus disease 2019 (COVID-19) and severe renal impairment has been approved; however, limited clinical data exist. Accordingly, we aimed to compare outcomes and adverse events associated with remdesivir in hospitalized patients with COVID-19, with and without severe renal impairment. Methods: Hospitalized patients with COVID-19 undergoing a 5-day remdesivir course at Taipei Veterans General Hospital from April 1 to July 31, 2022, were enrolled. Comparative analysis of outcomes and safety between patients with or without severe renal impairment (estimated glomerular filtration rate of < 30 mL/min per 1.73 m2) were conducted. Prognostic factors associated with 28-day mortality in patients with severe renal impairment were investigated using logistic regression analysis. Results: A total of 671 hospitalized patients, including 132 patients with severe renal impairment, who received a 5-day course of remdesivir were analyzed. The 28-day mortality was higher in patients with severe renal impairment than in patients without severe renal impairment (15.2% vs. 7.8%). The proportion of patients with acute kidney injury (AKI) and deteriorated liver function after completing remdesivir therapy was similar between the patients with and without severe renal impairment, and the recovery rate of AKI was similar in both groups. The sequential organ failure assessment score was an independent factor associated with 28-day mortality in patients with severe renal impairment. Conclusions: Remdesivir was well-tolerated in hospitalized patients with COVID-19, regardless of renal function. Our findings support the recent recommendation to administer remdesivir in patients with severe renal impairment.